Teacher responses to the Namibian education reform : a case study of two Caprivi schools - Kamwi, Kamwi Kenneth (Rhodes University, Faculty of Education, Department of Education, 2002)
Effective implementation of education reforms consists of alterations in curriculum materials, instructional practices and behaviour, beliefs and understandings on the part of the teachers involved in the reform (Fullan and Hargreaves, 1993: 5). A process of implementation is therefore, a learning process, learning how to do something new (ibid.). This study was done to establish how Biology teachers in Caprivi have responded to the reform process ten years down the line. I used a qualitative case study of two secondary schools. Four Biology teachers, two school principals and two groups of learners participated in the study. Data was collected by means of interviews, lesson observations, a workshop, and school inventories. The data was analysed within an interpretive framework. The results of the study show a move into 'activity-based teaching'. It shows a shift from the traditional transmission teaching approach. In general teachers seem to equate 'activity-based teaching' with the learner-centred approach.
Keywords: Education -- Namibia; Education and state -- Namibia; Educational change -- Namibia